The variability in the relationship between black carbon and carbon monoxide over the eastern coast of China: BC aging during transport - Guo, Q. F.; Hu, M.; Guo, S.; ZJ Wu; Peng, J. F.; Y.S. Wu (Atmospheric Chemistry and Physics, 2017)
East Asia is a densely populated region with a myriad of primary emissions of pollutants such as black carbon (BC) and carbon monoxide (CO). To characterize primary emissions over the eastern coast of China, a series of field campaigns were conducted in 2011, including measurements from a ship cruise, island, and coastal receptor sites. The relationship between BC and CO is presented here for the first ship cruise (C1), the second ship cruise (C2), an island site (Changdao Island, CD), and a coastal site (Wenling, WL). The average BC mass concentrations were 2.43, 2.73, 1.09, 0.94, and 0.77 mu g m(-3) for CD, WL, C1-YS (Yellow Sea), C1-ES (East China Sea), and C2-ES, respectively. For those locations, the average CO mixing ratios were 0.55, 0.48, 0.31, 0.36, and 0.27 ppm. The high loadings of both BC and CO imply severe anthropogenic pollution over the eastern coast of China. Additionally, the linear correlation between BC and CO was regressed for each location. The slopes, i.e., the ratios of Delta BC to Delta CO derived from their relationship, correlated well with the ratios of diesel consumption to gasoline consumption in each province/city, which reveals vehicular emission to be the common source for BC and CO and that there are distinct fuel structures between North and South China. The Delta BC/Delta CO values at coastal sites (Changdao Island and Wenling) were much higher than those over the Yellow Sea and East China Sea, and the correlation coefficients also showed a decreasing trend from the coast to the sea. Therefore, the quantity of Delta BC/Delta CO and the correlation coefficients are possible indicators for the aging and removal of BC.
Keywords: budget; gaseous-pollutants; light-absorption; Meteorology & Atmospheric Sciences; optical-properties; organic aerosol; particles; period; regional receptor-site; soot; sulfuric-acid